At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the equation \(4x + 7 = 5x + 6\), follow these steps:
1. Move all terms involving \(x\) to one side and constants to the other side:
- Subtract \(4x\) from both sides to isolate the terms involving \(x\) on one side of the equation:
[tex]\[ 4x + 7 - 4x = 5x + 6 - 4x \][/tex]
Simplifying this, we get:
[tex]\[ 7 = x + 6 \][/tex]
2. Isolate the variable \(x\):
- Subtract 6 from both sides to move the constants to the left side of the equation:
[tex]\[ 7 - 6 = x + 6 - 6 \][/tex]
Simplifying this, we get:
[tex]\[ 1 = x \][/tex]
So the solution to the equation \(4x + 7 = 5x + 6\) is:
[tex]\[ x = 1 \][/tex]
1. Move all terms involving \(x\) to one side and constants to the other side:
- Subtract \(4x\) from both sides to isolate the terms involving \(x\) on one side of the equation:
[tex]\[ 4x + 7 - 4x = 5x + 6 - 4x \][/tex]
Simplifying this, we get:
[tex]\[ 7 = x + 6 \][/tex]
2. Isolate the variable \(x\):
- Subtract 6 from both sides to move the constants to the left side of the equation:
[tex]\[ 7 - 6 = x + 6 - 6 \][/tex]
Simplifying this, we get:
[tex]\[ 1 = x \][/tex]
So the solution to the equation \(4x + 7 = 5x + 6\) is:
[tex]\[ x = 1 \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.